Tasamuh Based E-Module Developtment in The Fiqih Subject for 10th Grade Students in Islamic Senior High School - Ratih Ratih; Fauzi Muharom (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2021)
The aim of this study is to produce the teaching material product in the form of tasamuh based e-module in the fiqih subject that have the accurate materials, feasible design, and materials that suitable for the 10th grade students of Madrasah Aliyah. The research method used in this study is Research and Development with the development model by Borg & Call (1983) which has been simplified, they are 1) Research & Information Collection, (2) Planning (3) Develop Preliminary Form of Product, (4) Preliminary Field Testing, and (5) Main Product Revision. This study reveals that; (1) the final product of this development is tasamuh based fiqh e-modul with the materials about corpse’s management in the perspective of 4 madzhab, (2) The result of the 2 material experts‘ trial test about the material accuracy contained in the teaching materials got the percentage of 90.83%, it shows that the accuracy of teaching materials is very accurate, (3) The result of the 2 media experts’ trial test about the design feasibility got the percentage of 91.6%, it shows that the teaching materials has the very feasible design, (4) the result of the fiqih teachers’ trial test showed the percentage of 88.33%, it shows that the developed e-module is suitable for the 10th grade students of Madrasah Aliyah.